Святилище Ареса в Коцюбинчиках на Західному Поділлі в контексті егейських впливів на пантеон царства сколотів - Бандрівський, М. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
An attempt of reconstruction of religion model, which existed in State of Scoloths, including Nevryda, in VII – VI centuries B. C. is made at the article on the base of known from literature and discovered sources. It is offered to interpret cult complex from Kotsjubynchyky in Ternopil’ region (the largest in Western Ukraine) not only as grandiose stone burial monument for members of ruling dynasties and aristocrats, but also as sanctuary of Ares.